Altruistic and self-serving goals modulate behavioral and neural responses in deception. Issue 1 (15th November 2017) - Cui, Fang; Wu, Song; Wu, Haiyan; Wang, Chengyao; Jiao, Can; Luo, Yuejia
Abstract: People tell lies not only for their own self-interests but sometimes also to help others. Little is known about the ways in which different types of goals modulate behaviors and neural responses in deception. The present study investigated the neural processes associated with spontaneous deception that occurs with altruistic reasons (i.e. the money would be donated to charity), self-serving reasons (i.e. the participant receives all of the money) and mixed goals (i.e. the money would be equally split between the participant and the charity). Altruistic motivation for deception reduced the intensity of moral conflict and the subsequent mental cost of resolving this conflict, reflected by a smaller N2–P3 effect in the purely altruistic condition. When making decisions about whether to lie, self-interest was a stronger motivator than others' interests, and the participants tended to lie more for themselves than for others. When the lie could be mutually beneficial for both of the self and others, the participants tended to lie even when they knew that they could be easily caught, but they actually lied for their own self-interest rather than for altruistic reasons. These findings shed light on the neural basis of 'good lies' and decision-making in mutually beneficial situations.